MIGRATION OF THE INTRAUTERINE CONTRACEPTIVE INTO THE BLADDER WITH THE FORMATION OF A SECONDARY STONE AND VAGINAL-VESICAL FISTULA - Павленко, Владимир Вячеславович; Каменева, Евгения Александровна; Кулева, Ольга Владимировна; Петришина, Татьяна Ивановна (Medicine in Kuzbass, 2024)
The paper presents a case of migration of an intrauterine contraceptive into the bladder cavity with the subsequent formation of a vaginal-vesical fistula and a secondary stone on an intrauterine contraceptive. The intrauterine contraceptive was removed by excision with a hook electron and traction for a foreign body without technical difficulties. The bladder was drained and the vaginal-vesicular fistula closed on its own.